MiR-146a down-regulates inflammatory response by targeting TLR3 and TRAF6 in Coxsackievirus B infection - Fei, Yanru (RNA, 2020)
Coxsackievirus B (CVB) is the major cause of human myocarditis and dilated cardiomyopathy. Toll-like receptor 3 (TLR3) is an intracellular sensor to detect pathogen's dsRNA. TLR3, along with TRAF6, triggers an inflammatory response through NF-κB signaling pathway. In the cells infected with CVB type 3 (CVB3), the abundance of miR-146a was significantly increased. The role of miR-146a in CVB infection is unclear. In this study, TLR3 and TRAF6 were identified as the targets of miR-146a. The elevated miR-146a inhibited NF-κB translocation and subsequently down-regulated proinflammatory cytokine expression in the CVB3-infected cells. Therefore, the NF-κB pathway can be doubly blocked by miR-146a through targeting of TLR3 and TRAF6. MiR-146a may be a negative regulator on inflammatory response and an intrinsic protective factor in CVB infection.